Gender as a predictor of attitude towards HIV counselling and testing amongst road safety personnel in Imo State, Nigeria (2012)
This study examined gender difference in attitude towards HIV Counselling and Testing (HCT) amongst Federal Road Safety Personnel (FRSC) personnel in Imo state exposed to Emotional Intelligence Therapy (EIT). Pretest-posttest control group quasi experimental design with 2x2x2 factorial matrix was adopted for the study. One hundred participants (Male=60; Female=40) with age range of 24 to 40 years (x =23.01; SD=1.12) were purposively drawn from two units of FRSC Imo Sector Command. Attitude towards HIV Antibody Testing Scale (r=0.89) was used for data collection. The data derived from the pre and post treatment assessments were subjected to Analysis of Covariance using pre-test scores as covariates. Results show that EIT was potent for modifying HCT attitude of the treated group in comparison with the control group [F (1, 99) =82.14, P<0.05). Gender and educational status have significant influence on treatment outcomes (t=1.53; DF= (1, 99), P=<0.05) and (F (1, 99) =45.08; P<0.05) respectively. Based on these findings, EIT is recommended therapy for improving HCT attitude among women in high HIV risky occupation in Nigeria. The outcomes have implications for programmers to be gender sensitive in development, implementation and evaluation of HIV intervention.